FAKTOR - FAKTOR YANG MEMPENGARUHI KEJADIAN HIPERTENSI PADA PRA LANSIA DI PUSKESMAS SANGKUNUR TAHUN 2019 - RAHMAH JULIANI SIREGAR (JURNAL ILMIAH KOHESI, 2021)
The type of research used is analytic study with cross sectional design. The population in this study were all prehypertensionsuffering as many as 55 people. The sample is the entire population number used as the sample that is asmuch as 55 people. Data were obtained from Puskesmas Sangkunur and through interview result using questionnaire. Theresults showed statistical test results of independent variables eating habits obtained means there is a significant influence ofindependent variables with the dependent variable. Physical activity obtained Sig value means there is a significant influenceindependent variables with dependent. Smoking habits obtained means there is a significant influence independentvariables with dependent. Gender obtained indigo means there is no significant influence of independent variable withdependent. Variables that affect the incidence of hypertension. Based on the results of the study concluded there is alifestyle influence on the incidence of hypertension in the elderly and expected the patient is able to maintain a healthylifestyle so as to further improve the health status.